2021
DOI: 10.1007/s11055-021-01108-z
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 (COVID-19) as a Predictor of Neuroinflammation and Neurodegeneration: Potential Treatment Strategies

Abstract: The SARS-CoV-2 (COVID-19) pandemic has attracted attention to the challenge of neuroinflammation as an unavoidable component of viral infections. Acute neuroinflammatory responses include activation of resident tissue macrophages in the CNS followed by release of a variety of cytokines and chemokines associated with activation of oxidative stress and delayed neuron damage. This makes the search for treatments with indirect anti-inflammatory properties relevant. From this point of view, attention is focused on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The latter is characterized by high serum levels of pro-inflammatory biomarkers (such as CRP, IL-6, etc.) and by an uncontrolled inflammatory process that, if not inhibited, induces multi-organ failure [46][47][48]. Therefore, the significant reduction in inflammatory status that we observed in our um-PEA-treated patients seems to contrast the onset of the systemic inflammation and the CS.…”
Section: Discussionmentioning
confidence: 63%
“…The latter is characterized by high serum levels of pro-inflammatory biomarkers (such as CRP, IL-6, etc.) and by an uncontrolled inflammatory process that, if not inhibited, induces multi-organ failure [46][47][48]. Therefore, the significant reduction in inflammatory status that we observed in our um-PEA-treated patients seems to contrast the onset of the systemic inflammation and the CS.…”
Section: Discussionmentioning
confidence: 63%
“…So far, anti-inflammatory therapy has not been shown to be useful in affecting long COVID cognitive function, including dexamethasone, and tocilizumab ( 70 , 71 ).…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%
“…In a study conducted in vitro, it was found that infection with SARS-CoV-2 led to an increase in the levels of CX3CL1, also known as fractalkine (FKN) (Blanco-Melo et al, 2020). The release of chemokines in response to neuroinflammation can set off a cascade of signaling pathways, one of which is oxidative stress, which ultimately results in the death of neurons (Putilina & Grishin, 2021).…”
Section: Effec Ts Of Covid -19-induced Immune Re S P On S E On the B B Bmentioning
confidence: 99%